Improved filtration performance and antifouling properties of polyethersulfone ultrafiltration membranes by blending with carboxylic acid functionalized polysulfone. Issue 14 (19th February 2018) - Wu, Xing; Xie, Zongli; Wang, Huanting; Zhao, Chen; Ng, Derrick; Zhang, Kaisong
Abstract : Ultrafiltration membranes with improved filtration performance and antifouling properties have been synthesized through blending polyethersulfone with carboxylic acid functionalized polysulfone. Abstract : To improve the filtration performance and antifouling properties of ultrafiltration (UF) membranes, novel polymer blend UF membranes were fabricated in this study. Carboxylic acid functionalized polysulfone (PSFNA) was synthesized by modifying polysulfone (PSF) with 6-hydroxy-2-naphthoic acid (HNA). A series of polymer blend UF membranes were fabricated by adding different amounts of PSFNA into polyethersulfone (PES) to form a homogeneous casting solution. The influences of PSFNA on the morphology, thermal stability, hydrophilicity, filtration performance and antifouling properties of the blend membranes were investigated. The results indicated that by adding PSFNA into PES membranes, the finger-like pores in the membranes became larger, and the porosity and surface hydrophilicity of the membranes were improved. Compared with the pristine PES membrane, PES/PSFNA membranes demonstrated improved filtration performance, resulting in both increased water flux and higher bovine serum albumin (BSA) rejection. At a feed pressure of 0.1 MPa, the PES/PSFNA membrane with 4.0 wt% PSFNA had a pure water flux of 478 L m −2 h −1, which was 1.7 times higher compared with the PES membrane (287 L m −2 h −1 ). In addition, the antifouling properties of PES membranes were also enhanced with the addition of PSFNA. The PES/PSFNA membranes with 3.0 wt% PSFNA had a total fouling ratio (TFR) of 49.6%, as compared with 62.5% for PES membranes.